A Global Retrospective Study on Human Cases of Tetrodotoxin (TTX) Poisoning after Seafood Consumption. Issue 7 (2nd October 2020) - Guardone, Lisa; Maneschi, Andrea; Meucci, Valentina; Gasperetti, Laura; Nucera, Daniele; Armani, Andrea
ABSTRACT: The presented global retrospective study on human cases of tetrodotoxin (TTX) intoxication caused by seafood consumption was aimed at updating the relative risk according to seafood product categories (fish, gastropods, cephalopods, arthropods) and geographical areas. Overall, 3032 cases from five continents were collected, mainly from Asia. Over half of them were attributed to fish, followed by gastropods, arthropods and cephalopods. In South East and East Asia, intoxications derived from all the aforesaid seafood product categories, locally sourced; in Oceania, Sub-Saharan Africa and Central-South America, intoxication were from local pufferfish. In Europe, dated cases were caused by imported Asian products, as in North America. However, recent intoxications in Spain, Middle East and North Africa, caused by locally caught products, confirm the occurrence of TTX even in areas previously not affected by this public health issue.